2014
DOI: 10.1111/josh.12127
|View full text |Cite
|
Sign up to set email alerts
|

The FRIENDS Emotional Health Program for Minority Groups at Risk

Abstract: Adaptations to existing evidence-based programs for implementation with specific minority groups at risk represents a promising approach to promote emotional health in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 41 publications
3
12
0
2
Order By: Relevance
“…The key results revealed that following the EHC child‐reported depression and anxiety symptoms and teacher‐reported depression symptoms were reduced in at‐risk children with the effect size ranging from medium to large. These findings with 3rd and 4th grade children were similar to other studies with older at‐risk children who significantly benefited from a school‐based CBT preventive program (Cardemil, Reivich, Beevers, Seligman, & James, ; Iizuka, Barrett, Gillies, Cook, & Miller, ; Mazurek Melnyk, Kelly, & Lusk, ). Together, these findings suggest that school‐based interventions using cognitive behavioral theory had a positive effect on children who demonstrated elevated internalizing symptoms.…”
Section: Discussionsupporting
confidence: 86%
“…The key results revealed that following the EHC child‐reported depression and anxiety symptoms and teacher‐reported depression symptoms were reduced in at‐risk children with the effect size ranging from medium to large. These findings with 3rd and 4th grade children were similar to other studies with older at‐risk children who significantly benefited from a school‐based CBT preventive program (Cardemil, Reivich, Beevers, Seligman, & James, ; Iizuka, Barrett, Gillies, Cook, & Miller, ; Mazurek Melnyk, Kelly, & Lusk, ). Together, these findings suggest that school‐based interventions using cognitive behavioral theory had a positive effect on children who demonstrated elevated internalizing symptoms.…”
Section: Discussionsupporting
confidence: 86%
“…Targeted prevention and intervention efforts across various attributes of bullying and discrimination, particularly incidents perceived to be motivated by sexual orientation and weight, are warranted. Promoting youth coping skills should be incorporated into school health education curricula and school‐based mental health promotion …”
Section: Implications For School Healthmentioning
confidence: 99%
“…É um programa estruturado de prevenção universal, que foi reconhecido pela OMS como eficaz no fortalecimento de habilidades socioemocionais, resiliência e na prevenção de transtornos relacionados à ansiedade e depressão (WHO, 2004). Além disso, ele vem sendo aplicado em diversos países tendo resultados positivos quanto sua eficácia e efetividade (Stallard et al, 2007;Kosters et al, 2012;Iizuka, Barrett, Gillies, Cook & Miller, 2014). Segundo Vianna, Campos e Fernandez (2009) o programa Friends é considerado, ao redor do mundo, o programa de maior efetividade na prevenção de ansiedade.…”
Section: Método Friendsunclassified